Outcomes and complications following ABO‐incompatible kidney transplantation performed after desensitization by semi‐selective immunoadsorption: a retrospective study - Speer, Claudius; Kälble, Florian; Nußhag, Christian; Becker, Luis Eduardo; Klein, Katrin; Sommerer, Claudia; Beimler, Jörg; Leo, Albrecht; Waldherr, Rüdiger; Mehrabi, Arianeb; Süsal, Caner; Zeier, Martin; et al. (Transplant international, 2019)
Because of the current organ shortage, ABO‐incompatible (ABOi) transplantations have been increasingly performed in recent years. The results seem comparable to those of compatible transplantations, but there have also been reports of increased side effects possibly because of the desensitization therapy.
Gesehen am 18.01.2021